KECERNAAN ENERGI DAN KECERNAAN NUTRIEN TOTAL PADA TERNAK SAPI PERAH YANG DIBERIKAN PAKAN LENGKAP BERBASIS TEBON JAGUNG - Klau, Maria Y.; Pendong, Abraham F.; Tuturoong, R.A.V.; Waani, Merci. R. (ZOOTEC, 2020)
ENERGY DIGESTIBILITY AND TOTAL DIGESTIBLE  NUTRIENT IN DAIRY COWS GIVEN COMPLETE FEED BASED ON  CORN FORAGE. The purpose of this research  was to examine the value of energy digestibility and total nutrient digestibility in dairy cows which are given complete feed based on corn forage. 14 head of cattle with age ± 6-8 years weighing 300-400 kg were used in this study. This biological experiment used a statistical analysis of the T test with unequal variations (t-test two sample assuming unequel variance). The treatments consists of: Ra (30% Concentrate + 70% Corn forage), and Rb (30% Concentrate + 35% Corn forage + 35% King Grass). The results showed that the energy intake both of treatments(Ra and Rb) were not significantly different (P <0.05) while the energy digestibility and total digestible nutrient of the Rb treatment were significantly higher (P <0.05) than Ra treatment. It can be concluded that feed treatment using of 30% oncentrate, 35% king grass, and 35% corn forage was obtained the best energy disgestibility and total digestible nutrient values.Keywords: energy digestibility, dairy cows. corn forage , king grass.